STRATEGI KOMUNIKASI KOMUNITAS RETIC DALAM MEMBENTUK PERILAKU PEDULI TERHADAP KELESTARIAN HEWAN BERJENIS REPTIL DI PEKANBARU - Agusthyo, Wafiq; lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Indonesia has a wealth of diverse fauna. A series of records and records held by the country's wealth. But Indonesia is also one of the contributors to the extinction of fauna in the world,The longer, the longer the list of fauna Indonesia are included in the category of endangered. Retic Pekanbaru is a community of animal lovers One reptile manifold. Retic community consisting of 30 people is concerned with the preservation of animal reptile with all sorts of activities in the community design in shaping the behavior of the animals concerned about the preservation of various reptiles in Pekanbaru.This research uses descriptive qualitative research methods. Informants consisted of five people who is the chairman and members of the Community RETICPekanbaru by using purposive. Data collected by observation, interview and documentation. To achieve the validity of the data in this study, researchers used the extension of participation and triangulation.The results showed that the Community RETIC Pekanbaru strategies targeting these communities seek to know who the target in order to establish an appropriate message. Community Retic also using electronic media (local radio and local television), social media (instagram), print media (newspapers). And in the delivery of his message Retic community has always stressed how important sustainability reptiles animals to be maintained so that shape the behavior of the animals concerned about the preservation of Reptiles. The role of communicators in the community this Retic is considered by all members of the community, the communicator must have a pull-factor source and credibility of the source so that the message can be understood by the communicant and the message also can be responsible for the truth.Keyword : Communication Strategy In The Form of Conduct Retic Community Care for Animals Sustainabillity in The Reptile manifold Pekanbaru